Acoustic performance of natural fiber reinforced polymer composites: Influencing factors, future scope, challenges, and applications. Issue 3 (22nd December 2021) - Das, Partha Pratim; Chaudhary, Vijay; Ahmad, Furkan; Manral, Ankit; Gupta, Sumit; Gupta, Pallav
Abstract: Noise pollution caused by urbanization and industrial development must be effectively controlled to provide a pleasant living atmosphere. Different synthetic fiber materials have good acoustic performance, yet synthetic fiber materials have a high cost and have adverse effect on the environment. Natural fibers are a good alternative to synthetic fibers in terms of acoustic properties and they are also less expensive and have less environmental impact. Several factors affects the acoustic behavior of natural fiber reinforced polymer composites (NFRPCs). The present article focuses on the effect of different processing methods, reinforcement architecture, fiber diameter, laminate thickness and density on the acoustic performance of NFRPCs. Reinforcement architecture has been proved to be the best option in order to tailor the various acoustic properties of the composite laminates without even changing other physical properties. The challenges, future scope and potential applications of natural fibers in acoustic applications (home theaters, offices, cinema halls, automobiles, etc.) have also been discussed. Abstract : The article includes how the reinforcement architecture of the fiber affects the acoustic behavior of natural fiber reinforced polymer composites (NFRPCs). Also, the various processing methods of NFRPCs are highlighted along their effect on acoustic behavior. Various theoretical and experimental methods to evaluate acoustic properties are identified along with their advantages and disadvantages. Due to the promising properties of natural fibers and their composites, they are constantly being used in wide range of applications for various acoustic applications. In the coming years, the practical value of natural materials/fibers for acoustic applications will increase by developing different combinations of composites which can be used for acoustic applications.